2016
DOI: 10.1007/s12035-016-9709-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Co-transplantation of Olfactory Ensheathing Cells and Schwann Cells on Local Inflammation Environment in the Contused Spinal Cord of Rats

Abstract: Inflammatory response following spinal cord injury (SCI) is important in regulation of the repair process. Olfactory ensheathing cells (OECs) and Schwann cells (SCs) are important donor cells for repairing SCI in different animal models. However, synergistic or complementary effects of co-transplantation of both cells for this purpose have not been extensively investigated. In the present study, we investigated the effects of co-transplantation of OECs and SCs on expression of pro- or anti-inflammatory factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…30,31 OECs can significantly reduce the expression of CCL2 and CCL3, reducing the activation of astrocytes, which leads to scar repair. 24 In addition, this study also showed that intrathecal grafted OECs resulted in substantial improvement in motor function by higher open-field BMS score. This is the "golden standard" to prove a therapy method is effective.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…30,31 OECs can significantly reduce the expression of CCL2 and CCL3, reducing the activation of astrocytes, which leads to scar repair. 24 In addition, this study also showed that intrathecal grafted OECs resulted in substantial improvement in motor function by higher open-field BMS score. This is the "golden standard" to prove a therapy method is effective.…”
supporting
confidence: 55%
“…[21][22][23] As SCI induces apoptosis or death of neurons and scar formation, we examined neuron regeneration and scar bridging to evaluate the therapeutic efficacy of LP-transplanted OECs. [24][25][26] Figure 3 shows that the number of endogenous neurons, from −400 to +400 µm, in OEC-transplanted mice is more than that in SCI mice without engraftment. Intrathecal transplanted OECs could promote neuron regeneration in this range.…”
mentioning
confidence: 99%
“…OECs are highly phagocytic cells that surround olfactory neurons and rapidly clear pathogens and debris at the CNS-nasal mucosa border. 38,152,178,188 They also generate a favorable environment by expressing neurotrophins and facilitating olfactory regeneration after injury. 9 OECs have been harvested from the olfactory bulb and the nasal mucosa for transplant into the cord.…”
Section: Olfactory Ensheathing Cellsmentioning
confidence: 99%
“…These results suggest that OECs and SC's co-transplantation can promote the change of the macrophage phenotype from M1 secreting IFN-γ, to M2 secreting IL-4. The induction to M2 reduces ICs infiltration in the damaged site, regulates inflammatory factors and chemokine expression, which provide ICs environment for SCI repair [65].…”
Section: Olfactory Ensheating Cells Transplantation In Spinal Cord Inmentioning
confidence: 99%